Efektivitas Ekstrak Herbal Meniran, Kunyit, dan Temulawak terhadap Pertumbuhan, Persentase Karkas, dan Lemak Abdomen Ayam Broiler - Puji Astuti; Heru Suripta (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the effect of administering a combination of meniran (Phyllanthus niruri), turmeric (Curcuma longa), and temulawak (Curcuma xanthorrhiza) water extract in drinking water on the performance and carcass quality of broiler chickens. A total of 100 days-old broiler chickens (DOC) were used in the study which was arranged in a Completely Randomized Design with 4 treatments and 5 replications, each containing 5 chickens. The treatments consisted of: P0 (control, without extract), P1 (25% meniran: 25% turmeric: 50% temulawak), P2 (25%: 50%: 25%), and P3 (50%: 25%: 25%). The extract was given in drinking water as much as 10 ml/liter from 7 to 35 days of age. The parameters observed included feed consumption, water consumption, daily body weight gain (ADG), feed conversion (FCR), carcass percentage, and abdominal fat. The results showed that the herbal extract treatment had a significant effect (P<0.05) on feed consumption, carcass percentage, and abdominal fat, but was not significantly different on water consumption, ADG, and FCR. Treatment P1 showed the best performance, with the highest feed consumption, the highest carcass (72.86%), and the lowest abdominal fat (1.72%). It was concluded that the administration of a combination of meniran, turmeric, and temulawak water extract with a ratio of 25:25:50 significantly increased the growth efficiency and carcass quality of broiler chickens, and could be an alternative safe and effective natural feed additive.